Managing employees disciplinary at Petronas Dagangan Berhad “A question on the compliance towards the Malaysian employment laws” / Aina Nadia Ghazali - Ghazali, Aina Nadia (2016)
The purpose of this research is to examine the compliance level on managing employees disciplinary at the Petronas Dagangan Berhad towards the Malaysian Employment Laws. This research is to analyze misconduct cases that are reported at Petronas Dagangan Berhad from 2013 to 2015; examine the compliance level of procedures in managing the employees disciplinary at the workplace towards Malaysian Employment Law which are Employment Act 1955 and Industrial Relation Act 1967; examine the Petronas Dagangan Berhad policies and procedure in managing misconduct at workplace which is PETRONAS Code of Conduct and Business Ethics Guide and study the roles of Employee Relation Department in managing disciplinary matters. The data gathered for this research comes from the respondents who are involving in managing misconduct cases at Petronas Dagangan Berhad and an analysis of company’s data based on the misconduct cases that have been reported. The results of this research indicate that Petronas Dagangan Berhad has a high level of compliance towards the Malaysian Employment Laws in the scope of policies and procedures as well as practices in managing employees disciplinary at the workplace. Besides, all the recommendations that have been made to the organization hopefully will lead to the decreasing number of employees committed the misconduct.